CORTICOSTEROID AS TREATMENT OF ALOPECIA AREATA - Junika Putri, Ni Putu; Sugiritama, I Wayan (E-Jurnal Medika Udayana; vol 2 no5(2013):e-jurnal medika udayana)
Alopecia areata is a common cause of alopecia nonscarring. Incidence alopecia areata 1-2% of the population, with the same ratio in both sexes, and occurs in all racial groups. The characteristics of alopecia areata lesions usually develop bald patch with one or more round or oval in hair bearing areas of the body, especially on the scalp. Alopecia areata is an inflammatory disease, autoimmune mediated by T lymphocytes disease Therapy for alopecia areata is to suppress immune and inflammatory processes that occur in alopecia areata. Corticosteroid therapy is one modality of therapy for alopecia areata, because it has anti-inflammatory and immunosuppressive effects. Several methods corticostreroid administration consist of intralesional injection, topical, and systemic therapies
Keywords: alopecia areata, corticosteroid